Chemogenetic Silencing of Differentiating Cortical Neurons Impairs Dendritic and Axonal Growth - Gasterstädt, Ina; Schröder, Max; Cronin, Lukas; Kusch, Julian; Rennau, Lisa-Marie; Mücher, Brix; Herlitze, Stefan; Jack, Alexander; Wahle, Petra (Frontiers in Cellular Neuroscience, 2022)
Electrical activity is considered a key driver for the neurochemical and morphological maturation of neurons and the formation of neuronal networks. Designer receptors exclusively activated by designer drugs (DREADDs) are tools for controlling neuronal activity at the single cell level by triggering specific G protein signaling. Our objective was to investigate if prolonged silencing of differentiating cortical neurons can influence dendritic and axonal maturation. The DREADD hm4Di couples to Gi/o signaling and evokes hyperpolarization via GIRK channels. Hm4Di was biolistically transfected into neurons in organotypic slice cultures of rat visual cortex, and activated by clozapine-N-oxide (CNO) dissolved in H2O; controls expressed hm4Di, but were mock-stimulated with H2O. Neurons were analyzed after treatment for two postnatal time periods, DIV 5-10 and 10-20. We found that CNO treatment delays the maturation of apical dendrites of L2/3 pyramidal cells. Further, the number of collaterals arising from the main axon was significantly lower, as was the number of bouton terminaux along pyramidal cell and basket cell axons. The dendritic maturation of L5/6 pyramidal cells and of multipolar interneurons (basket cells and bitufted cells) was not altered by CNO treatment. Returning CNO-treated cultures to CNO-free medium for 7 days was sufficient to recover dendritic and axonal complexity. Our findings add to the view that activity is a key driver in particular of postnatal L2/3 pyramidal cell maturation. Our results further suggest that inhibitory G-protein signaling may represent a factor balancing the strong driving force of neurotrophic factors, electrical activity and calcium signaling.